Sister Carrie - Dreiser, Theodore, 1871-1945 (Penguin twentieth-century classics., 1994)
Young Caroline Meeber leaves home for the first time and experiences work, love, and the pleasures and responsibilities of independence in late-nineteenth-century Chicago and New York.